Etnicitás és kulturalizmus a Bánságban : 1910 - Kókai, Sándor (Közép-Európai Közlemények, 2013)
The Bansag was a unique intercultural area in the historical Hungary, since then it mostly disappeared as the ethnical and linguistic rate changed. At the same time it is still a special cultural geographical region in the Carpathian-Basin. The Bansag’s cultural diversity is originated thanks to these nations: Romanians, Germans, Hungarians, Serbs, Croatians, Jewish, Bulgarians, Slovaks, Czechs, Gypsies, Turkish. The religious variety is also characteristic because of the large number of religions (Orthodox, Catholicism, Protestant and Jewish denomination). The Bansag was the model of peaceful coexistence between 1718 and 1918. Nowadays the maintenance of intercultural heritage is in danger. The region lost the multilingual character, which would mean connection with West-Europe.